Protection of the Land Rights of the Paser Indigenous Tribe in the National Capital Region Nusantara - Andy Usmina Wijaya; Fikri Hadi; Muhamad Chaidar (CV. Era Digital Nusantara, 2025)
Abstract: The regulation regarding the relocation of the new capital city has sparked pros and cons within the community across various categories; one pertains to the land occupied, maintained, and nurtured by the indigenous Paser tribe residing in the area. Their land has provided sustenance for their survival and that of their descendants. The relocation of the capital city to their territory raises questions concerning the land they have cared for all this time. Article 18B, paragraph 2 of the 1945 Constitution acknowledges the importance of customary law in developing national law. Purpose: This paper will explain the protection to Paser Indigenous Tribe regarding the Land Rights after the relocation of the capital city. Design/Methodology/Approach: The type of research is normative law, The approaches used are the statute approach and the conceptual approach. Findings: The main results or discoveries of the research presented briefly. Present the article’s findings based on the analysis and discussion done in the paper. Originality/value: The background of the object being studied is the same Indigenous communities affected by national-scale strategic projects. The difference in this context is that it focuses on the indigenous communities affected by the development project of the National Capital in Nusantara.